Hydrothermal-induced changes in the gel properties of Mung bean proteins and their effect on the cooking quality of developed compound noodles - Diao, Jingjing; Tao, Yang; Chen, Hongsheng; Zhang, Dongjie; Wang, Changyuan (Frontiers in Nutrition, 2022)
Mung bean proteins (MBPs) are highly nutritious food ingredients, but their lack of gluten limits their use in staple foods such as noodles. In this study, MBPs were modified by hydrothermal treatment, and their gel properties and changes in their secondary structure were analyzed at different heating temperatures (25 °C, 65 °C, 75 °C, 85 °C, 95 °C, and 105 °C), moisture contents (0%, 15%, 20%, 25%, 30%, and 35%), and hydrothermal treatment times (0, 15, 30, 45, 60, and 75 min). Thereafter, the modified MBPs (MMBPs) were added to wheat noodles at substitution levels of 3%, 6%, and 9% to evaluate their effect on the quality of the noodles. The results showed that the hydrothermal treatment significantly improved the gel properties and water absorption capacity of the MBPs and slightly increased their disulfide bond content. When MBPs with a 25% moisture content were heated at 85 °C for 60 min, their gel properties notably improved, and their structural changes were maximal. The structural changes revealed that the MBP molecule formed a macromolecular polymer because a significant protein band appeared at about 66.2 kDa. Secondary structure and microstructure analyses revealed that the MBP structure was significantly damaged and that the β-sheet structure increased because of changes in the degree of aggregation between the protein molecules. Compared to the untreated MBPs, the MMBPs significantly improved the cooking quality and texture properties of the noodles, and the addition amount reached more than 6%, whereas that of the untreated MBPs was less than 3%. An analysis of changes in the water distribution, rheological properties, and microstructure revealed that intermolecular cross-linking occurred between the MMBPs and wheat dough, which improved the quality of the MMBP-treated noodles. The findings demonstrated that the MMBPs obtained by hydrothermal treatment had a positive effect on the wheat dough properties and noodle quality. These results provide a technical foundation for incorporating novel protein supplements into staple foods.